2016
DOI: 10.1590/1807-2577.09816
|View full text |Cite
|
Sign up to set email alerts
|

Oral conditions and body weight in children from a public school in Manaus, AM, Brazil

Abstract: ResumoIntrodução: Estudos têm apontado para relações existentes entre prevalência de cárie e doença periodontal e ocorrência de sobrepeso ou obesidade, porém poucos estudos foram conduzidos em crianças. Objetivo: Avaliar a relação entre doença periodontal, cárie e peso corporal em crianças de uma escola pública de Manaus -AM, Brasil. Material e método: Cento e sessenta e nove crianças foram incluídas no estudo. Registros foram obtidos, tais como, dentes cariados, perdidos e obturados na dentição permanente (CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
2
12
0
Order By: Relevance
“…In our study, there is no difference in caries experience between normal weight and overweight children. This finding is consistent with studies done by Tuomi [23], Chen et al [24], Moreira et al [7], and Assi et al [25].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there is no difference in caries experience between normal weight and overweight children. This finding is consistent with studies done by Tuomi [23], Chen et al [24], Moreira et al [7], and Assi et al [25].…”
Section: Discussionsupporting
confidence: 93%
“…In this study 5% of all children were identified as underweight, 66.5% as normal weight, 17.7% as overweight and 10.8% as obese, which corresponds to the results of the National Representative Study on the prevalence of overweight and obese children in Bulgaria. 6 The current investigation demonstrated a nonsignificant correlation between body weight and periodontal health, which coincides with much other research on this topic [13][14][15] but conflicts with others. Sfasciotti G et al in a cross-sectional study among 100 children of 7-12 years old found out that a full-mouth plaque score value equal to 21.86% was observed in the group of non-obese patients against 50.08% in the group of overweight/obese patients.…”
Section: Discussionsupporting
confidence: 76%
“…The BMI is often used to calculate the nutritional status of the individual. [ 1 2 3 4 5 ] The obesity has been increasingly reported among the school children these days due to the closure of the live classes due to COVID and the absence of physical activity. In our study, we evaluated the OH, DC, for the various BMI categories.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are similar to the previous studies. [ 2 3 4 5 6 7 ] Compared to the western countries the food habits vary in India as majority are vegetarians and the nutritional levels are satisfactory. The DC has been noted higher in previous research among the obese subjects, as is in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation